Thermodynamic analysis of dry autothermal reforming of glycerol - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Fuel Processing Technology, 2010)
{Dry autothermal reforming of glycerol uses a combination of dry (CO(2)) reforming and partial oxidation reactions to produce syngas rich product stream. Thermodynamic equilibrium data for dry autothermal reforming of glycerol was generated for temperature range 600-1000 K . 1 bar pressure, OCGR [feed O(2)/C (C of glycerol only) ratio] 0.1 to 0.5 and CGR [feed CO(2)/glycerol ratio] 1 to 5 and analyzed. The objective of the paper is to identify the thermodynamic domain of the process operation, study the variation of product distribution pattern and describe the optimum conditions to maximize yield of the desired product and minimize the undesired product formation. Higher OCGR and higher CGR yielded a syngas ratio (similar to 1), with lower carbon and methane formation, while lower CGR and lower OCGR yielded good hydrogen and total hydrogen, with low water and CO2 production. The best thermoneutral condition for DATR of glycerol operation was seen at a temperature of 926.31 K at 1 bar pressure
Keywords: CO(2) reforming; Dry reforming; Glycerol reforming; Syngas production; Thermodynamic modeling